2021
DOI: 10.1021/acs.orglett.1c01957
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Asymmetric Trifluoromethylated Allylic Alkylation of Pyrazolones Enabled by α-(Trifluoromethyl)alkenyl Acetates

Abstract: The first asymmetric trifluoromethylated allylic alkylation of pyrazolones using α-(trifluoromethyl)alkenyl acetates as a novel trifluoromethylated allylation reagent is described, affording various functionalized chiral pyrazolones containing a trifluoromethylated allyl substituent in high yields with excellent regio-/enantio-/diastereoselectivities. Mechanistically, the doublebond migration of α-(trifluoromethyl)alkenyl acetates in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene is initial and interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The optimization of the bases showed that the reaction did not carry out normally when DBU was replaced by other bases (Table 2, entries 1–7). This is due to other bases can not promote the double bond migration of α ‐(trifluoromethyl)alkenyl acetates, which has been verified in our previous study [12h,i] . When dioxane was replaced by THF, toluene, DMF, 2‐Me‐THF, CH 3 CN, ClCH 2 CH 2 Cl, DME, MTBE, lower enantioselectivity or yield was observed (Table 2, entries 8–15).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The optimization of the bases showed that the reaction did not carry out normally when DBU was replaced by other bases (Table 2, entries 1–7). This is due to other bases can not promote the double bond migration of α ‐(trifluoromethyl)alkenyl acetates, which has been verified in our previous study [12h,i] . When dioxane was replaced by THF, toluene, DMF, 2‐Me‐THF, CH 3 CN, ClCH 2 CH 2 Cl, DME, MTBE, lower enantioselectivity or yield was observed (Table 2, entries 8–15).…”
Section: Resultssupporting
confidence: 60%
“…We recently showed that α‐ (trifluoromethyl)alkenyl esters could be used for the synthesis of various trifluoromethyl‐ containing compounds, [12] including pyrazolones [12h] and 3‐substituted oxindoles [12i] , which prompted us to develop a method which would provide straightforward access to enantioenriched trifluoromethyl‐containing glycine ester derivatives (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the Zhou group developed α-(trifluoromethyl)alkenyl acetates 72 as new trifluoromethylation allylation synthons and employed them in the asymmetric trifluoromethylated allylic alkylation of pyrazolones 2a with the Pd/ L7 complex as the chiral catalyst (Scheme 15). 35 The resulting pyrazolones 73 , containing trifluoromethyl groups, were obtained in high yields with excellent regioselectivities and stereoselectivities. Interestingly, the double bond migration of 72 in the presence of the strong base 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) was initially carried out to generate the chiral π-allyl palladium complex 66 .…”
Section: -Mono-substituted Pyrazolone As a Synthonmentioning
confidence: 99%
“…Later, the same group also developed an oxidative method with alkenes [13] . Further studies employing Pd(0) catalysts for the synthesis of compounds bearing CF 3 substituted allylic side chains, [14] sequential Mannich additions/allylations [15] and allenylations were reported [16] . In addition, Rh catalysts in combination with methylalkynes were used [17] …”
Section: Introductionmentioning
confidence: 99%